PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP LUAS PENGUNGKAPAN SUKARELA PADA LAPORAN TAHUNAN - Azzahra, Alfizah (Jurnal Ilmiah Mahasiswa FEB, 2020)
This research aims to examine the effect of corporate governance mechanism on voluntary disclosure in companiesâ€™ annual report. The size of the board commissioners, independent board of commissioners, institutional ownership and family ownership are the independent variables used as the proxy of corporate governance mechanism measures; the voluntary disclosure is the dependent variable measured utilizing items of disclosure index; and the company size and public accounting firm size are the control variables. This research uses secondary data from the annual report of consumer goods companies listed on Indonesia Stock Exchange between 2016 and 2018. The samples consist of 27 companies selected by purposive sampling method. The multiple linear regression analysis result indicates that the size of the board commissioners, independent board of commissioner, and family ownership have an effect on voluntary disclosure, while institutional ownership has no effect on voluntary disclosure. As the institutions focuses on the output of financial statement, additional information on voluntary disclosure lacks attention.Â Keywords: voluntary disclosure, corporate governance, size of the board commissioners, independent board of commissioners, institutional ownership, family ownership